Facilitation or inhibition? Impact of CEO’s financial background on industrial AI transformation of manufacturing companies - Xu, Peng; Zhang, Zichao (Frontiers in Psychology, 2023)
Taking manufacturing listed companies in Shanghai and Shenzhen stock exchanges within the framework of enterprise groups from 2014 to 2020 as research samples, this paper empirically tests the impact of CEO's financial background on industrial AI transformation of manufacturing enterprises based on the Upper Echelons Theory and Imprinting Theory. It is found that CEO's financial background significantly inhibits the industrial AI transformation of manufacturing enterprises, and when the CEO works part-time in the parent company, it will strengthen the negative impact of CEO's financial background on industrial AI transformation. Further research shows that enterprise financialization plays a partial intermediary role between CEO's financial background and industrial AI transformation; Compared with private enterprise groups, the inhibiting effect of CEO financial background on industrial AI transformation is stronger in state-owned enterprise groups; CEOs with non-banking financial background have a stronger inhibitory effect on industrial AI transformation.